Development of a Novel Transparent Flexible Capacitive Micromachined Ultrasonic Transducer - Pang, Da-Chen (Sensors (Basel), 2017)
This paper presents the world’s first transparent flexible capacitive micromachined ultrasonic transducer (CMUT) that was fabricated through a roll-lamination technique. This polymer-based CMUT has advantages of transparency, flexibility, and non-contacting detection which provide unique functions in display panel applications. Comprising an indium tin oxide-polyethylene terephthalate (ITO-PET) substrate, SU-8 sidewall and vibrating membranes, and silver nanowire transparent electrode, the transducer has visible-light transmittance exceeding 80% and can operate on curved surfaces with a 40 mm radius of curvature. Unlike the traditional silicon-based high temperature process, the CMUT can be fabricated on a flexible substrate at a temperature below 100 °C to reduce residual stress introduced at high temperature. The CMUT on the curved surfaces can detect a flat target and finger at distances up to 50 mm and 40 mm, respectively. The transparent flexible CMUT provides a better human-machine interface than existing touch panels because it can be integrated with a display panel for non-contacting control in a health conscious environment and the flexible feature is critical for curved display and wearable electronics.